2019
DOI: 10.1017/jns.2019.37
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with cod protein hydrolysate in older adults: a dose range cross-over study

Abstract: A large proportion of older adults are affected by impaired glucose metabolism. Previous studies with fish protein have reported improved glucose regulation in healthy adults, but the evidence in older adults is limited. Therefore, we wanted to assess the effect of increasing doses of a cod protein hydrolysate (CPH) on postprandial glucose metabolism in older adults. The study was a double-blind cross-over trial. Participants received four different doses (10, 20, 30 or 40 mg/kg body weight (BW)) of CPH daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Nevertheless, there have been multiple studies recently published investigating the antidiabetic and satiating effect of a cod protein hydrolysate; however, there appears to be no significant effect on plasma hormones, blood glucose, or satiety with one study reporting a reduction in plasma insulin. [35,[89][90][91] Initially this appears to be due to a very low dosage regimen (a maximum of 4 g per day) but a separate study performed by Hovland et al showed an effect on glucose tolerance by a cod protein supplement through ingestion of 2.5 g per day for 8 weeks. [92] The important differentiation between these studies is likely that Hovland et al used an unhydrolyzed cod protein supplement, highlighting that the bioactivity of the protein is impacted by the hydrolysis process, and in this case hydrolysis may have negatively impacted the bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there have been multiple studies recently published investigating the antidiabetic and satiating effect of a cod protein hydrolysate; however, there appears to be no significant effect on plasma hormones, blood glucose, or satiety with one study reporting a reduction in plasma insulin. [35,[89][90][91] Initially this appears to be due to a very low dosage regimen (a maximum of 4 g per day) but a separate study performed by Hovland et al showed an effect on glucose tolerance by a cod protein supplement through ingestion of 2.5 g per day for 8 weeks. [92] The important differentiation between these studies is likely that Hovland et al used an unhydrolyzed cod protein supplement, highlighting that the bioactivity of the protein is impacted by the hydrolysis process, and in this case hydrolysis may have negatively impacted the bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous human intervention studies have reported improvements in postprandial glucose and insulin levels after supplementation with fish protein [ 20 , 28 ], and similar findings have been observed in animal studies [ 14 , 29 , 30 ]. Furthermore, we have previously shown that the postprandial insulin concentration in serum was significantly lower in normal-weight adults given one single dose of CPH compared to control (unhydrolyzed casein), without an effect on glucose levels [ 31 ]. Considering that the subjects in the current trial had MetS, the lack of effect is surprising, but there could be several reasons for this.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, adjusting the CPH dosage to the body weight of each participant could have further strengthened the design, as it would reduce the effect of variation in body weight. It was not practically feasible, and we chose to use a dose similar to what has previously been effective [15,36,45]. Thirdly, the lack of a power analysis is a weakness when interpreting the data, but there was no relevant data to base such calculation upon.…”
Section: Discussionmentioning
confidence: 99%